2004
DOI: 10.1002/jmv.20195
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of the dengue virus is cell cycle modulated in HepG2, but not vero cells

Abstract: While many studies have investigated the relationship between cell type and dengue virus infection, no study to date has examined the effect of cell physiology on permissiveness to infection. Unsynchronized and artificially synchronized cell populations at different stages of the cell cycle of two cell types (Vero and HepG2) were examined for permissiveness to infection by two dengue virus serotypes (serotypes 2 and 3) by determining both the levels of virus produced as well as the percentage of cells infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…However, DENV-2 infection was not found to affect the cell cycle in either of these two cell types. A study examining the effect of the cell cycle on DENV replication showed that the effects may be cell type specific [80], which may explain the results of this study using DENV-2 infected A549 cells. For a number of other viruses it has been shown that viral replication arrests the cell cycle at the G2/M transition, including HCV [81][83].…”
Section: Resultsmentioning
confidence: 63%
“…However, DENV-2 infection was not found to affect the cell cycle in either of these two cell types. A study examining the effect of the cell cycle on DENV replication showed that the effects may be cell type specific [80], which may explain the results of this study using DENV-2 infected A549 cells. For a number of other viruses it has been shown that viral replication arrests the cell cycle at the G2/M transition, including HCV [81][83].…”
Section: Resultsmentioning
confidence: 63%
“…In the present study, the drastic reduction in cell viability in both infected MCF7 and MCF7-CR after 12 hpi was strongly suggestive of the involvement of cell cycle phases in the infectivity and cytotoxicity of NDV. Virus internalization was previously shown to be affected by these phases [30]. In addition, cisplatin resistance caused changes in cell cycle regulatory proteins which affect their way of responding to the drug [31].…”
Section: Discussionmentioning
confidence: 99%
“…These cells were chosen since cells of the hepatocyte lineage are implicated in the in vivo pathogenesis of DENV infection where patients with dengue fever and DHF often showed evidence of liver injury 10. Electron micrograph of HepG2 cells infected by dengue virus showed presence of intracellular virus particles originating from its replication site, the endoplasmic reticulum 11.…”
Section: Discussionmentioning
confidence: 99%